2013
DOI: 10.4067/s0718-95162013005000022
|View full text |Cite
|
Sign up to set email alerts
|

Agronomic properties and characterization of rice husk and wood biochars and their effect on the growth of water spinach in a field test

Abstract: This study compared the agronomic properties of rice husk biochar (RHB) and wood biochar (WB) and investigated their effect on the growth rate of water spinach in a field experiment. Each biochar type was tested at 5 different rates of 4.0, 3.0, 2.0, 1.0 and 0.5 kg m3 , respectively. The results detailing the growth of water spinach showed that the application of rice husk biochar improves biomass production. The WB added to soil increased the plant weight of water spinach by increasing the root size and leaf … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
28
0
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(44 citation statements)
references
References 21 publications
5
28
0
4
Order By: Relevance
“…The higher BC doses resulted in higher barley grain yields relative to the control. Increases in plant height, biomass growth and grain yield under biochar amendments have been widely reported (Alburquerque et al, 2013;Baronti et al, 2010;Varela Milla et al, 2013). However, contrasting findings are also common (Mukherjee and Lal, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…The higher BC doses resulted in higher barley grain yields relative to the control. Increases in plant height, biomass growth and grain yield under biochar amendments have been widely reported (Alburquerque et al, 2013;Baronti et al, 2010;Varela Milla et al, 2013). However, contrasting findings are also common (Mukherjee and Lal, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, RH contains a high content of silicon and potassium nutrients. These properties indicate RH has great potential to be used as a soil amendment [11]. Moreover, [12] reported that RH could be used as a soil amendment, particularly, for improving soil physical properties by improving the porosity of soil.…”
Section: Introductionmentioning
confidence: 99%
“…The authors attributed these increases to the increase in soil fertility status improving nutrition required for maize grain quality improvement. There are also several reports on an increase in plant height, growth and grain quality with biochar application in crops [27][28][29], which indicate a positive effect of biochar on crops.Biochar addition to soils is expected to promote sustainable crop production through a positive effect on yield, but these may depend on the cropping seasons. For instance, Cornelissen et al [30] studied the effect of rice husk biochar and cacao shell biochar applied to Indonesia Utisol soil at rates of up to 15 t ha −1 and found that the maize yield with rice husk biochar become lower and faded in the second cropping while with cacao shell biochar was highest in the second cropping through third and fourth, but faded in the fifth cropping seasons.…”
mentioning
confidence: 99%
“…These lack of positive responses of crop yield could be attributed to the changes in biochar chemistry over time as it ages in the soil environment [34]. Hence, the properties of biochar responsible for crop improvement may be altered consequently leading to no effect on growth and yield.Several pieces of research have focused on biochar effects on grain crops, such as rice, maize, wheat and vegetable of which plant growth responses to biochar addition varied [19,21,24,27,28,32]. However, there is still a scarcity of information of biochar addition on sesame [35,36], indicating a need to generate understanding of how biochar addition can effectively be used to increase sesame production.…”
mentioning
confidence: 99%
See 1 more Smart Citation